Succinonitrile‐based solid‐state electrolytes for dye‐sensitised solar cells. (12th December 2013) - Byrne, Owen; Coughlan, Aoife; Surolia, Praveen K.; Thampi, K. Ravindranathan
Abstract Succinonitrile (SCN), a solid ion conductor (10−4 to 10−3 S/cm) in solid form at room temperature, is mixed with either 1, 2‐dimethyl‐3‐propylimidazoliuum iodide or 1‐butyl‐3‐methyl imidazolium iodide ionic liquids for forming a solid plastic phase electrolyte for use in dye‐sensitised solar cell (DSSC). Cells containing these two electrolytes showed best energy conversion efficiencies of 6.3% and 5.6%, respectively. The commonly used DSSC electrolyte additives inhibit the formation of the SCN plastic phase. However, for the first time, an SCN‐additive (additive = guanidinium thiocyanate) electrolyte composition is reported here, which remains as a solid at room temperatures. By using these new solid electrolytes, a simple and rapid single‐step filling procedure for making solid‐state DSSC is outlined. This process, which reduces the required manufacturing steps from four to one, is most suitable for continuous, high‐throughput, commercial DSSC manufacturing lines. These new electrolytes have been tested under low incident light levels (200 lx) to investigate their suitability for indoor DSSC applications. Copyright © 2013 John Wiley & Sons, Ltd.